Propriedades vibracionais de cristais de DL-leucina e L-prolina monohidratada submetidos a altas pressões - Abagaro, Bruno Tavares de Oliveira (2012)
We studied the stability of two types amino acid crystal: a racemic crystal, DL-leucine (C6H13NO2); and a chiral one; L-proline monohydrate (C5H9NO2.H2O). Both were subjected to high pressures. The structural properties at ambient conditions (with the hydrogen-bonds data) of each crystal type were presented. For the DL-leucine crystal, polarized Raman scattering measurements were made in three different scattering geometries. The classification of the normal modes of vibration was made in terms of representations of irreducible factors groups Ci (for the crystal of DL-leucine) and C2 (crystal of L-proline monohydrate). Based on studies already carried out previously, tentative assignments were proposed for the Raman bands observed for the two crystals. The high pressure Raman experiments were performed in a diamond anvil cell using mineral oil as pressure media. For the DL-leucine crystal, the maximum pressure was studied up to about 5 GPa. Among the various observed effects, we found the discontinuity of the wavenumber versus pressure curves between 2.4 and 3.2 GPa, both for the region of the external modes as for region of internal modes, particularly remarkable. These effects were interpreted as resulting from a gradual change of the molecular conformation of leucine molecules in the unit cell, culminating with change of hydrogen bonds in the interval where the phase transition is observed. This behaviour suggests that the DL-leucine crystal is more stable than the chiral L-leucine in the sense that while the former presents only one phase transition, the latter presents at least two different transitions in the same pressure range considered. For the L-proline monohydrated crystal, which was subject to pressures up to about 8.0 GPa, several induced effects by this thermodynamic parameter were observed in the Raman spectra, such as the appearance and disappearance of bands, discontinuities in the wavenumber versus pressure curves in the regions of external and internal modes and intensity relative changes. These changes point to the fact that between (i) 1.1 e 1.7 GPa and (ii) 4.5 e 5.0 GPa, this hydrated crystal undergoes phase transitions accompanied by conformational molecular changes in the unit cell.